Investigation of manoeuvring characteristics of the combined hinged agricultural units - Ярошенко, Павло Миколайович (Technology audit and production reserves, 2015)
This article deals with the problems of manoeuvrability of the combined hinged agricultural units, carrying out some technological operations within one pass on the field. The importance of these problems consists in the fact that the modern unit is a complex dynamic system, which must abbey the accurate directions of the machine-operator or other controlling operators. The given work investigates the manoeuvring characteristics of the combined hinged units on the example of soil cultivating and sowing unit. The influence of different manoeuvring indices on the unit operation in the whole as well as on the individual elements of its operation is revealed. Some indices describe the operating parameters of the unit in different ways. It concerns the turning and manoeuvrability parameters, that influence the size of turning stripes and the straightforwardness of sowing. The width of turning stripe at any field must be minimal from the points of view of operating width of the unit claw. Calculations have show that having overall dimensions, the unit will have large parameters of turning stripes the increasing of mass and the speed of movement will course the problems of possibility on the part of the field prepared for the sowing.